Analysis of Influence of Cyclone Seroja on Wave Height and Tide in the Indian Ocean - Umam, Choirul Umam; Pranowo, Widodo Setiyo; Azhari, Ferian Azhari; Hendra, Hendra; Setiyadi, Johar (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2024)
Tropical Cyclone Seroja, which occurred in the Indian Ocean, was characterized by maximum wind speeds of 70 knots. As part of the impact assessment associated with the cyclone, wave height observations were conducted along its track and tidal examinations were carried out at Cape Cuvier and Kupang tidal stations. Therefore, this research aims to analyze the relationship between wind speed and wave height, as well as the impact of Cyclone Seroja on waves and tide. The results showed that Cyclone Seroja reached a very high intensity with maximum wind speeds of 70 knots and maximum wave height of 14.24 meters on April 11, 2021, at 06:00 UTC. Regression analysis showed an R-squared value of 0.716, indicating that 71.6% of the variation in wave height can be explained by wind speed. The correlation value of 0.846 indicated a strong relationship between wind speed and wave height. This research also analyzed the changes in residual tide height at Cape Cuvier tidal station on April 11, 2021, with a maximum residual height of 0.57 meters. Wave height propagation from wave station 1487 significantly influenced the residual tide value at Cape Cuvier, with wave height of 11.790 meters and a propagation speed of 40.42 km/h. At Kupang tidal station, there was a residual height change of up to 0.27 meters, caused by influence of low pressure around wave station 239, with an average pressure of 1001 pHa and an average wave height of 3.89 meters, propagating towards the Kupang tidal station during the formation phase of Tropical Cyclone Seroja. Keywords: Cyclone; Seroja; Wave; Tide; Indian Ocean.